THE TREATMENT OF HEPATORENAL SYNDROME WITH TERLIPRESSIN: CONTINUOUS INTRAVENOUS INFUSION VS INTRAVENOUS BOLUSES A RANDOMISED CONTROLLED STUDY ON SYNDROME - ARYA, SURESH; JANNU, SHRAVAN; MATHUR, AMIT (International Journal of Current Pharmaceutical Research, 2023)
Objective: Hepatorenal syndrome (HRS) is a severe complication of cirrhosis, with terlipressin and albumin being the most common treatment. The study aimed to compare the effectiveness and safety of continuous intravenous infusion vs. intravenous boluses of terlipressin in treating type 1 h. Methods: A randomized controlled trial was conducted on cirrhosis patients with type 1 h. Patients were allocated to receive terlipressin via continuous infusion (TERLI-INF group) or intravenous boluses (TERLI-BOL group). Demographic, clinical, and laboratory data were collected, and treatment details were recorded. The primary endpoint was the frequency of drug-related adverse events. Secondary endpoints included therapy responsiveness and 90-day transplant-free survival. Results: Both groups exhibited similar baseline characteristics. While treatment length and cumulative albumin doses were comparable, TERLI-INF patients received lower terlipressin doses. Severe treatment-related adverse events differed between groups. Univariate analysis identified several baseline parameters significantly associated with response to terlipressin. The study supports continuous terlipressin infusion's superiority in treating type 1 h, with lower adverse event rates and improved patient response. Conclusion: The study concludes that continuous intravenous terlipressin infusion is safer and more effective in treating type 1 h in decompensated cirrhosis patients compared to intravenous boluses. Lower terlipressin dosages were effective in continuous infusion, indicating improved safety. The MELD score was an independent predictor of response, and therapy responsiveness was associated with improved 90 d survival.